University Research Management: An academic setting for Social Appropriation of Knowledge - Becerra, Luis Eduardo; Zarate Rueda, Ruth; Rodríguez Quiñónez, Diana Alexandra (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2015)
The accelerated pace of a complex society identified by the economic, social and environmental phenomena, the political context and cultural homogeneity, is the result of technological and scientific progress of globalization that has permeated the life quality of people to unsustainable conditions of poverty and inequality, affecting human development, social welfare and dignity. Being a priority that the technological development meets the needs of the population of a country at local and regional levels, industrial University of Santander (UIS) assumes the challenge of initiating the project "Model Management University Research" that allows, from his research work, to achieve the quality, efficiency, effectiveness and pedagogical relevance to the socialappropriation of knowledge in order to concernthe strengthening of capacities of individuals, the understanding of their environment and the contribution of the integral development of society. This study is oriented from systematic methodology five projects in 2005, using data collection instruments: the semistructured interview, the record of experiences and adiscussion group. The results emphasize the use of ICTs for generating academic resource productivity and innovation processes in response to the social needs of the population.